Developing mathematics comics through Instagram themed local culture as an alternative learning solution - Nana Apriana Nur Hidayah; Winarno Winarno; Muhammad Istiqlal (Universitas negeri Yogyakarta, 2022)
This study aimed to explore mathematical comics learning media through Instagram social media with the theme of local culture as an alternative learning solution that is feasible to use in terms of validity, practicality, and effectiveness. This study used the ADDIE development model. Analysis, to determine the problem and solution. Design, that is designing learning materials and objectives; sketching names, figures, and characters; compiling a script; making a storyboard; creating Instagram feed content. Development is the process of finishing the manufacture of products. The implementation of the product validation test was carried out by two experts in mathematics education and tested by students and teachers in a Junior High School in Salatiga. Evaluation is carried out as the final version of the material for further research based on teacher and student responses. Data collection methods in this study are observation, interviews, questionnaires, literature study, and documentation. The results showed that comics with local characters can engage students in learning mathematics. First, they might be interested to know the local culture and then were realized mathematical thinking. The data showed an average validity of 4.15 with a valid category, average practicality of 4.27 categorized as practical, and an average evaluation test obtained a result of 8.5 so it was categorized as effective on student learning outcomes. Therefore, when creating comics for learning in social media, using local culture is suggested.